Biodegradable poly (lactic acid)/poly (ethylene glycol) reinforced multi-walled carbon nanotube nanocomposite fabrication, characterization, properties, and applications - Ahmad, Ahmad Fahad; Ab. Aziz, Sidek; Obaiys, Suzan Jabbar; Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Samikannu, Kanagesan; Aliyu, Umar Sa'as (MDPI, 2020)
This paper presents the electromagnetic interference properties of multi-walled carbon nanotubes (MWCNTs) as a novel nano-reinforcement filler in poly (lactic acid) (PLA)/poly (ethylene glycol) (PEG) polymer matrix that was prepared via melt blending mode. Plasticization of PLA was first carried out by PEG, which overcomes its brittleness problem, in order to enhance its flexibility. A waveguide adapter technique was used to measure the dielectric properties εr , and S-parameters reflection (S11) and transmission (S21) coefficients. The dielectric properties, microwave attenuation performances, and electromagnetic interference shielding effectiveness (EMISE) for all the material under test have been calculated over the full X-Band (8–12 GHz) due to its importance for military and commercial applications. The prepared samples were studied while using X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), Fourier transforms infrared spectroscopy (FTIR), mechanical properties measurements, as well as thermogravimetric analysis (TGA). The results showed that the dielectric properties increased with increased multi-walled carbon nanotubes (MWCNTs) filler, as well as the shielding effectiveness of the MWCNT/PLA/PEG nanocomposites increased with the increasing of MWCNTs. The highest SE total value was found to be 42.07 dB at 12 GHz for 4 wt.% filler content. It is also observed that the attenuation values of the nanocomposites increased with an increase in MWCNTs loading, as well as the power loss values for all of the samples increased with the increase in MWCNTs loading, except the amount of the transmitted wave through the nanocomposites.